In vitro resistance profile of hepatitis C virus NS5A inhibitor velpatasvir in genotypes 1 to 6. Issue 8 (16th May 2019) - Dvory‐Sobol, Hadas; Han, Bin; Lu, Julia; Yu, Mei; Beran, Rudolf K.; Cheng, Guofeng; Martin, Ross; Svarovskaia, Evguenia; Mo, Hongmei
Abstract: Velpatasvir is a pan‐genotypic hepatitis C virus (HCV) NS5A inhibitor, which is used with sofosbuvir for treatment of infection with HCV genotypes 1‐6. In vitro resistance studies were performed to characterize NS5A changes that might confer reduced velpatasvir susceptibility in vivo. Resistance selection studies using HCV replicon cells for subtypes 1a, 1b, 2a, 2b, 3a, 4a, 5a and 6a identified NS5A resistance‐associated substitutions (RASs) at nine positions, most often 28M/S/T, 31F/I/M/P/V and 93D/H/N/S. In subtype 1a, RASs were selected at positions 31 and/or 93, while in subtype 1b, replicons with two or more RASs at positions 31, 54 or 93 were selected. Y93H was selected in subtypes 1a, 1b, 2a, 3a and 4a. In subtype 5a or 6a, L31P or P32L/Q was selected, respectively. Velpatasvir susceptibility of 358 replicons from genotypes 1 to 6 containing one or more NS5A RASs was also evaluated. The majority (63%) of subtypes 1a and 1b single RAS‐containing replicons retained susceptibility to velpatasvir (<2.5‐fold change in EC50 ). High levels of resistance to velpatasvir were observed for six single mutants in subtype 1a, including M28G, A92K, Y93H/N/R/W and for one mutant, A92K, in subtype 1b. Most single mutants in subtypes 2a, 2b, 3a, 4a and 5a displayed low levels of reduced velpatasvir susceptibility. High‐level resistance was observed for C92T and Y93H/N in subtype 2b, Y93H/S in 3a, and L31V and P32A/L/Q/R in 6a, and several double mutants in these subtypes. Overall, velpatasvir maintained activity against most common RASs that are known to confer resistance to first‐generation NS5A inhibitors.